ANALISIS PESAN STRATEGI KOMUNIKASI PEMASARAN COOLANT DALAM MEMBENTUK POSITIONING - Malta Christina Prasetya; Sampoerno - (Cakrawala Jurnal Penelitian Sosial, 2014)
Coolant is new product of isotonic drink, but as the trading by, Coolant decided to withdraw from the isotonic market. Realizing the market of isotonic drink has already been competitive and full of market leader, Coolant chose to create new sub category; positions as “body cooling drink”. To introduce the positioning to the market place and audience, Coolant recruited a well-known advertising agency in Indonesia, Dwi Sapta IMC since 2011. To play the marketing communication strategy, Coolant and Dwi Sapta IMC have run some campaign strategies such as advertising, brand activation, direct selling, and social media activation that led to introduce it’s positioning to public. Based on the pre-research, there was tendency in which consumers haven’t known Coolant as body cooling drink yet. This research is about the marketing communication strategy while the analysis unit is the message content in television advertisement and social media activation as these two are the marketing communication strategy that reaches whole target of audience and market of Coolant in Indonesia. The result shows Coolant is already representing it’s positioning as the body cooling drink by television commercial and social media activation. Coolant use photogenes, trick effect, pose, and texts that build audience knowledge about Coolant’s positioning. Though indeed the messages which have delivered through the communication strategy couldn’t build well-known image of positioning as consumer thought about Coolant yet. There must also some other factors besides marketing communication strategy that contribute to consumer understanding about one’s product. Keywords : Coolant, Marketing Communication Strategy, positioning, message.